KEPENTINGAN INDONESIA MELAKUKAN KERJA SAMA DENGAN PERANCIS DALAM BIDANG ANTARIKSA TAHUN 2017 - Nela Arsita; Ahmad Jamaan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The research aims to explain Indonesia's interest in space sector cooperation with France. Indonesia represented by LAPAN in collaboration with CNES, the French space agency on February 27, 2017. The areas of cooperation are satellite-based remote sensing data and their utilization, space and atmospheric science, micro and small satellites, space technology, issues related to conservation regulation, and the operation of satellites and balloons. The need on space technology for Indonesia is crucial because of the condition in Indonesia is extremely broad consisting thousands of islands, rich nature, and frequent natural disasters. So that the development of the technology is carried out to answer Indonesia's national interests in utilization in various fields, these are science, civil, and security. However, since the Indonesian national space agency was formed in 1963, the mastery of Indonesian space technology has not been independent due to the lack of government support in financing. In order to achieve this desire, Indonesia is conducting international cooperation. This study revealed the reason Indonesia partnering with France to increase the capacity and mastery of Indonesia's space technology. This is based on the capabilities of France and the similarity in the focus of developing space technology between Indonesia and France, namely the use of space technology for science, environment and maritime affairs. Keywords: Space, CNES, National Interests, International Cooperation, LAPAN